Discovering covalent cyclic peptide inhibitors of peptidyl arginine deiminase 4 (PADI4) using mRNA-display with a genetically encoded electrophilic warhead - Isabel R. Mathiesen; Ewen D. D. Calder; Simone Kunzelmann; Louise J. Walport (Communications Chemistry)
Abstract Covalent drugs can achieve high potency with long dosing intervals. However, concerns remain about side-effects associated with off-target reactivity. Combining macrocyclic peptides with covalent warheads provides a solution to minimise off-target reactivity: the peptide enables highly specific target binding, positioning a weakly reactive warhead proximal to a suitable residue in the target. Here we demonstrate the direct discovery of covalent cyclic peptides using encoded libraries containing a weakly electrophilic cysteine-reactive fluoroamidine warhead. We combine direct incorporation of the warhead into peptide libraries using the flexible in vitro translation system with a peptide selection approach that identifies only covalent target binders. Using this approach, we identify potent and selective covalent inhibitors of the peptidyl arginine deiminase, PADI4 or PAD4, that react exclusively at the active site cysteine. We envisage this approach will enable covalent peptide inhibitor discovery for a range of related enzymes and expansion to alternative warheads in the future.